2018
DOI: 10.3389/fphys.2018.01453
|View full text |Cite
|
Sign up to set email alerts
|

Arrhythmogenic Mechanisms in Heart Failure: Linking β-Adrenergic Stimulation, Stretch, and Calcium

Abstract: Heart failure (HF) is associated with elevated sympathetic tone and mechanical load. Both systems activate signaling transduction pathways that increase cardiac output, but eventually become part of the disease process itself leading to further worsening of cardiac function. These alterations can adversely contribute to electrical instability, at least in part due to the modulation of Ca2+ handling at the level of the single cardiac myocyte. The major aim of this review is to provide a definitive overview of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 257 publications
(314 reference statements)
3
43
0
Order By: Relevance
“…Abnormal Ca 2+ handling in cardiomyocytes has been increasingly implicated in the development of HF and has been shown to influence excitation-contraction coupling (ECC) and cell function, which leads to systolic dysfunction and arrhythmias (Johnson and Antoons, 2018). Recent studies have revealed that intracellular Ca 2+ dynamics are impaired before myocardial contractility is weakened.…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal Ca 2+ handling in cardiomyocytes has been increasingly implicated in the development of HF and has been shown to influence excitation-contraction coupling (ECC) and cell function, which leads to systolic dysfunction and arrhythmias (Johnson and Antoons, 2018). Recent studies have revealed that intracellular Ca 2+ dynamics are impaired before myocardial contractility is weakened.…”
Section: Introductionmentioning
confidence: 99%
“…Then, following the removal of the agonists, we studied the time course of regression, specific pathways that were regulated during regression, and we studied these processes in both males and females. Iso and Ang II are known to act through different pathways with Iso activating adrenergic receptors that are a class of G-protein coupled receptors on the cell surface that cause a canonical signaling cascade leading to increased concentration of Ca 2+ in the cytosol (36) . This increase ultimately results in faster contractions of the cardiomyocytes and mimics the increased work load observed in the disease state.…”
Section: Discussionmentioning
confidence: 99%
“…The following sections will provide further insights into intracellular Ca 2+ handling maladies in the most prevalent inherited and acquired arrhythmia syndromes, caused by channelopathies and defects in Ca 2+ handling genes. Ca 2+ handling defects also have an arrhythmogenic role in diseases, such as heart failure and cardiomyopathies, however they are beyond the scope of the present review [see recent reviews (Coppini et al, 2018;Johnson and Antoons, 2018;Denham et al, 2018)].…”
Section: Biexcitabilitymentioning
confidence: 99%